2012
DOI: 10.1016/j.drugalcdep.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Carisoprodol tolerance and precipitated withdrawal

Abstract: Aims Carisoprodol is a muscle relaxant that acts at the GABAA receptor. Concerns about the abuse liability of carisoprodol are increasing, but evidence that carisoprodol produces tolerance and a significant withdrawal syndrome has yet to be established. The purpose of the current study was to determine if repeated administration of carisoprodol produces tolerance and withdrawal signs in a mouse model. Methods Carisoprodol (0, 100, 200, 300, or 500 mg/kg bid, i.p.) was administered to Swiss-Webster mice for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The dangers associated with carisoprodol abuse, such as psychomotor impairment and severe withdrawal that may lead to seizures and death, are well-documented (Adams et al, 1975; Elder, 1991; Littrell et al, 1993; Reeves and Parker, 2003; Rust et al, 1993; Zacny et al, 2011, 2012). Precipitated withdrawal studies in mice have demonstrated tolerance to carisoprodol develops in as few as four doses (Gatch et al, 2012). In recent years, the ready availability of carisoprodol via internet pharmacies has led to increased recreational use of carisoprodol.…”
Section: Introductionmentioning
confidence: 99%
“…The dangers associated with carisoprodol abuse, such as psychomotor impairment and severe withdrawal that may lead to seizures and death, are well-documented (Adams et al, 1975; Elder, 1991; Littrell et al, 1993; Reeves and Parker, 2003; Rust et al, 1993; Zacny et al, 2011, 2012). Precipitated withdrawal studies in mice have demonstrated tolerance to carisoprodol develops in as few as four doses (Gatch et al, 2012). In recent years, the ready availability of carisoprodol via internet pharmacies has led to increased recreational use of carisoprodol.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐Dealkylation of carisoprodol catalyzed by the cytochrome P450 (CYP) isoform CYP2C19 in the liver results in meprobamate, which also has the ability to enter the CNS . As the midbrain‐forebrain‐extrapyramidal circuit with its focus in the nucleus accumbens has been linked mechanistically to substance abuse, psychoactive drug and metabolite concentrations measured from this site were expected to yield the most relevant information regarding mechanistic and behavioral correlates studied in experimental animals …”
Section: Resultsmentioning
confidence: 99%
“…[31] As the midbrain-forebrain-extrapyramidal circuit with its focus in the nucleus accumbens has been linked mechanistically to substance abuse, [32] psychoactive drug and metabolite concentrations measured from this site were expected to yield the most relevant information regarding mechanistic and behavioral correlates studied in experimental animals. [10,11] NanoESI, DART and ASAP were evaluated regarding their applicability of chromatography-free MS to carisoprodol and meprobamate analyses in microdialysis samples. Desalting of brain microdialysates is essential for nanoESI; however, it can be done rapidly as part of sample preparation by using ZipTips.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carisoprodol abuse causes psychomotor impairment and severe withdrawal that may predispose to seizures and death (Bramness et al, 2004;Fass, 2010;Zacny and Gutierrez, 2011;Reeves et al, 2012). Tolerance to carisoprodol develops relatively quickly, facilitating the problems associated with withdrawal (Reeves and Burke, 2010;Gatch et al, 2012). Indeed, considering its alarming abuse rate, carisoprodol was controlled as a Schedule IV substance at the federal level effective January 2012 (Reeves et al, 2012).…”
Section: Introductionmentioning
confidence: 99%